Estrategia psicopedagógica Abrapalabra para la comprensión lectora en una estudiante de cuarto grado de la escuela municipal Ecológica, periodo 2023 - Quizhpe Ochoa, Gema Lizbeth (2023)
The present degree work, denominated: Abrapalabra psycho-pedagogical strategy for reading comprehension in a fourth-grade student at the Ecological municipal school, period 2023, had as general objective: to strengthen reading comprehension through the use of activities based on the Abrapalabra educational software in a fourth grade student at the Ecological municipal school, period 2023. It was carried out under a qualitative, descriptive approach, with the case study method. The techniques used were: the semi-structured interview, the recording sheet, and the pre- and post-test of the reading comprehension test of progressive linguistic complexity. The sampling was intentional, where the student with reading comprehension difficulties participated, for the analysis and interpretation of the information obtained, data triangulation and profiles of the instrument results were worked on. To evaluate the impact of the application of the psychopedagogical strategy, the pre and post test were used. The results of the pre-test showed that the student was at level 1, with a mastery of understanding words and simple sentences. After the application of the psychopedagogical strategy abrapalabra, an interactive educational software. It was evaluated by applying the post test, in which the student obtained a level 3, with a mastery of reading comprehension of simple texts; Therefore, it is concluded that the application of a psycho-pedagogical strategy based on educational software such as Abrapalabra, significantly strengthens students' reading comprehension.